Conductive, Anti-Corrosion, Self-Healing Smart Coating Technology Incorporating Graphene-Based Nanocomposite Matrix - Benavides-Guerrero, Jaime; Banerjee, Debika; Gedamu, Dawit; Gerlein, Luis Felipe; Cloutier, Sylvain G. (Frontiers in Materials, 2022)
Chromate conversion coatings have been in service for decades providing robust corrosion protection to a wide variety of aluminum alloys. However, it is also known that anti-corrosive coatings containing Cr6+ contributes to DNA damage, cause cancer and are not environmentally friendly. Consequently, regulatory restrictions over the use Cr6+ were established to mitigate the environmental damage and health problems. To answer to this hurdle and to meet the emergent need for environmentally friendly anti-corrosive coatings, we have successfully developed an innovative coating that combines anti-corrosive, low electrical resistance, and self-healing properties. First, we present two different coatings, that aim to display low electrical resistance properties: one containing only graphene and the other containing Zn nanoparticles and graphene. Confocal laser imaging and SEM microscopy was used to observe the morphology of the coatings. The electrical resistance was measured using the 4-wire connection Kelvin method. We compare the anticorrosive response for both coatings under neutral salt spray test (NSSt). Raman spectroscopy was performed before and after to understand the effect of NSSt corrosive species on the coatings. Then, we select the coating with lower electrical resistance, and we program on it a self-healing mechanism to boost its life service. Finally cyclic voltammetry is performed to confirm the excellent blocking properties of the tested coatings. All the coatings presented in this work are applied on aluminum AA2024T351 and the optimal spray parameters for nanofillers dispersion are obtained. Our findings show great potential for preventing corrosion and compatibility with fully automated large-scale applications in different fields such as aerospace, automotive, construction, submarines and many more.